A aprendizagem da circunferência na perspectiva da geometria analítica mediada pelo software educacional GeoGebra - Mesquita Filho, José Victor de (2014)
In this work, it was intended to analyze the effectiveness of using GeoGebra Educational Software as a pedagogical tool for the study of the circumference in the context of analytic geometry. The research methodology was quantitative and qualitative approach and the study was performed in a public school State network of Fortaleza with a class of six students in the 3rd year of high school. To this end, applied to this group a pre-test to diagnose the previous knowledge then, there was a pedagogical intervention with an activities module, mediated by GeoGebra, allowing to analyze if this mediation favored the student’s understanding about in circumference. Later, the Group was tested with a post-test. After these steps, a final survey results led us considerations, confirming the objectives of research. In the body of the work was done a survey on the PCN and the teaching of mathematics, a description of the potential applications of GeoGebra to teach the circumference and the facilitation of teacher relationship x student. The theoretical foundation was based on authors such as Even (2004); Borba & Penteado (2007); Araújo e Nóbriga (2010); D’Ambrósio e Barros (1990) and official publications.